Informationsrecht@KIT - 15 Jahre Zentrum für Angewandte Rechtswissenschaft - Dreier, Thomas [Hrsg.]Spiecker gen. Döhmann, Indra [Hrsg.] (Schriften des Zentrums für Angewandte Rechtswissenschaft / ZAR, Zentrum für Angewandte Rechtswissenschaft, Karlsruher Institut für Technologie, 2015)
How can information law contribute to the activities of researchers, technicians and engineers? In what ways can law and information technology interact in a meaningful way? Is the law necessarily hampering innovation-driven technologies? The Center for applied legal studies (ZAR) at the Karlsruhe Institute of Technology (KIT) tries to provide answers to these questions. The volume assembles some answers given at the occasion of a symposium held at the occasion of the Centers 15th birthday.